It's Not Robotic: Barriers to Navigating Academic Integrity & the Role of Emotions - Scurr, Cory D (Canadian Perspectives on Academic Integrity, 2023)
In December, 2022, Conestoga College’s Academic Integrity Office launched an all-faculty survey on Academic Integrity. It was sent to just under 2,500 full-time and part-time faculty, and we received 989 faculty responses, or a 40% response rate. Focus Groups were also conducted to enrich our findings with qualitative data. Generally, this survey is being conducted to better understand how faculty interact with the institution’s academic integrity policies and procedures and to identify faculty interpretation, and possible improvements to supports and resources. In particular, we are keen to ascertain data on two important, yet neglected, questions: What are the barriers faculty experience when navigating academic integrity violations and do these vary depending on faculty type (Full-Time vs. Part-Time). How do discrete emotions impact faculty when navigating academic integrity violations, and do emotions impact penalty decisions? It her chapter titled, “Impediments to Reporting Contract Cheating: Exploring the Role of Emotions” in A Research Agenda for Academic Integrity (Ed. T. Bretag, 2020), Felicity Prentice states, “if emotional responses by academic staff to breaches of academic integrity affect judgement and decision-making, […] it is timely to address this as a potentially significant avenue for research” (p. 70). Potentially significant avenue for research, indeed. Overall, participants will glean an understanding of the barriers faculty face as well as how emotions may influence the process of navigating academic integrity.